2018
DOI: 10.1101/461236
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ENvironmental Dynamics Underlying Responsive Extreme Survivors (ENDURES) of Glioblastoma: a Multi-disciplinary Team-based, Multifactorial Analytical Approach

Abstract: Although glioblastoma is a fatal primary brain cancer with a short median survival of 15 months, a small number of patients survive more than 5 years after diagnosis; they are known as extreme survivors (ES). Due to their rarity, very little is known about what differentiates these outliers from other glioblastoma patients. For the purpose of identifying unknown drivers of extreme survivorship in glioblastoma, we developed the ENDURES consortium (ENvironmental Dynamics Underlying Responsive Extreme Survivors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…For a long time, the "extreme survivors" have baffled researchers and clinicians in the field-these are generally defined as glioblastoma patients who live >5 years with their disease. There is a wide range of variability in the field, but recent survival rates at 5 years are estimated to be close to 10% (44). Patients who live longer are more likely to become extreme survivors, studies have found, with those having reached the 2.5-year mark more likely to survive to 5 years (45,46).…”
Section: Survival and Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…For a long time, the "extreme survivors" have baffled researchers and clinicians in the field-these are generally defined as glioblastoma patients who live >5 years with their disease. There is a wide range of variability in the field, but recent survival rates at 5 years are estimated to be close to 10% (44). Patients who live longer are more likely to become extreme survivors, studies have found, with those having reached the 2.5-year mark more likely to survive to 5 years (45,46).…”
Section: Survival and Prognosismentioning
confidence: 99%
“…Patients who live longer are more likely to become extreme survivors, studies have found, with those having reached the 2.5-year mark more likely to survive to 5 years (45,46). Additional studies are trying to focus on these survivors, collecting their numbers across institutions to determine patterns and predictive factors (44).…”
Section: Survival and Prognosismentioning
confidence: 99%